Modelling and Design of a Current Controller for Light Rail Regenerative Inverter System - Hilmi M.H.Z.; Toh C.L.; Ooi P.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Electric current control; Electric inverters; Electric power transmission networks; Energy conversion; Harmonic analysis; Light rail transit; Braking energy; Current controller; Energy storage modules; Harmonics distortion; Inverter system; Light rail vehicle; Three-phase voltage source inverters; Total harmonics distortions; Passive filters